Programmed genome editing of the omega-1 ribonuclease of the blood fluke, Schistosoma mansoni - Wannaporn Ittiprasert; Victoria H. Mann; Shannon E. Karinshak; Avril Coghlan; Gabriel Rinaldi; Geetha Sankaranarayanan; Apisit Chaidee; Toshihiko Tanno; Chutima Kumkhaek; Pannathee Prangtaworn; Margaret Mentink‐Kane; Christina J. Cochran; et al. (2019)
CRISPR/Cas9-based genome editing has yet to be reported in species of the Platyhelminthes. We tested this approach by targeting omega-1 (ω1) of Schistosoma mansoni as proof of principle. This secreted ribonuclease is crucial for Th2 polarization and granuloma formation. Schistosome eggs were exposed to Cas9 complexed with guide RNA complementary to ω1 by electroporation or by transduction with lentiviral particles. Some eggs were also transfected with a single stranded donor template. Sequences of amplicons from gene-edited parasites exhibited Cas9-catalyzed mutations including homology directed repaired alleles, and other analyses revealed depletion of ω1 transcripts and the ribonuclease. Gene-edited eggs failed to polarize Th2 cytokine responses in macrophage/T-cell co-cultures, while the volume of pulmonary granulomas surrounding ω1-mutated eggs following tail-vein injection into mice was vastly reduced. Knock-out of ω1 and the diminished levels of these cytokines following exposure showcase the novel application of programmed gene editing for functional genomics in schistosomes.